The Role of Compensation and Job Satisfaction on Employee Performance of Bakery Store in Sidoarjo, Indonesia - Frasisca Ovi Mareta; As'at Rizal (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this study was to determine the partial and simultaneous influence between leadership, compensation and job satisfaction on the performance of UD Griya Pangan Bersama employees as well as the dominant variables between leadership variables, compensation and job satisfaction on employee performance of UD Griya Pangan Bersama, This research uses quantitative research methods. The results showed that Leadership had a positive and significant effect on the performance of UD Griya Pangan Bersama employees, as evidenced by the significance value of tcount of 0,000 <0,05; Compensation had a positive and significant effect on the performance of UD Griya Pangan Bersama employees, evidenced by the significance value of tcount of 0,002 <0,05; Job satisfaction has a positive and significant effect on the performance of UD Griya Pangan Bersama employees, as evidenced by the significance value of tcount of 0,000 <0,05; Leadership, compensation and job satisfaction have a positive and significant effect on the performance of UD Griya Pangan Bersama employees, as evidenced by the Fcount significance value of 0,000 <0,05; and Leadership has the most dominant influence on the performance of UD Griya Pangan Bersama employees, evidenced by the highest tcount of 4,463.